How will the public health committees develop after COVID-19 pandemic in China? Exploration from mixed methods study in Pingshan District, Shenzhen - Xu Shao; Xu Shao; Xiangling Wu (Frontiers Media S.A., 2024)
IntroductionThe Public Health Committee has a long-standing presence in the Chinese Constitution. During the pandemic, it served as a grassroots self-governance organization and made significant contributions to China's community epidemic prevention and control system. Currently, 24 provinces in China have promoted the establishment of community public health committees.MethodsTo gather data, we conducted semi-structured interviews (n = 48) with the heads of superior departments of public health committees, the heads of public health committees, and the heads of community health centers, exploring aspects such as organizational structure, job responsibilities, and job security. In parallel, we administered a capacity-building survey to a sample of 23 community residents (n = 1,986) and performed regression analysis. Finally, we examined the impact of gender, age, and education level on the development of public health committees.ResultsOur study reveals that the development of public health committees displays features of administration across various dimensions, including personnel appointment, top-level design, medical professionalism, funding path dependence, and data path dependence. However, the decision-making function of the organization does not exhibit a significant impact.DiscussionThe construction of the Public Health Committee should demonstrate an "autonomization-administration" pendulum effect. Currently, due to the absence of decision-making functions within the Public Health Committee, autonomous organizations are exhibiting characteristics of administration. To prevent excessive autonomization or administrative nature in the development of committees, public health policies are continuously being refined based on the unique characteristics of public health committee construction. During exceptional circumstances or the initial stages of development, the establishment of public health committees should be primarily guided by administrative principles, utilizing political momentum to drive their progress. In contrast, during routine establishment phases or later stages of development, the establishment of public health committees should be primarily led by autonomization, restoring their capacity for self-decision making. It is essential to fully leverage the role of grassroots self-governance organizations, relying on the community to engage in self-management, self-education, and self-service within public health committees.